Proposing TODD-graphene as a novel porous 2D carbon allotrope designed for superior lithium-ion battery efficiency - E. A. J. Santos; K. A. L. Lima; L. A. Ribeiro Junior (Scientific Reports, 2024)
Abstract The category of 2D carbon allotropes has gained considerable interest due to its outstanding optoelectronic and mechanical characteristics, which are crucial for various device applications, including energy storage. This study uses density functional theory calculations, ab initio molecular dynamics (AIMD), and classical reactive molecular dynamics (MD) simulations to introduce TODD-Graphene, an innovative 2D planar carbon allotrope with a distinctive porous arrangement comprising 3-8-10-12 carbon rings. TODD-G exhibits intrinsic metallic properties with a low formation energy and stability in thermal and mechanical behavior. Calculations indicate a substantial theoretical capacity for adsorbing Li atoms, revealing a low average diffusion barrier of 0.83 eV. The metallic framework boasts excellent conductivity and positioning TODD-G as an active layer for superior lithium-ion battery efficiency. Charge carrier mobility calculations for electrons and holes in TODD-G surpass those of graphene. Classical reactive MD simulation results affirm its structural integrity, maintaining stability without bond reconstructions at 2200 K.